Demography of Anoda cristata in wide- and narrow-row soyabean - Puricelli, Eduardo Carlos Jose Maria (2002)
The annual weed Anoda cristata is recognized as a problem of increasing importance in soyabean crops. As seeds are the only source for the renewal of A. cristata populations, knowledge of its seedbank characteristics and seed production is useful in improving weed management decisions. There is a lack of information about the effect of the planting pattern of soyabean on weed population dynamics. The effects of 70-cm and 35-cm soyabean row spacings on A. cristata seedbank, seedling recruitment and mortality, plant biomass, seed production and seed shed were determined. Soyabean density was higher in 35-cm row spacings as an increase in planting rate in narrow-row soyabean is recommended for producers in Argentina. The different planting patterns modified A. cristata demography through changes in plant biomass and, subsequently, in seed production. Seedling emergence, plant mortality and the pattern and duration of seed shed were similar in both planting patterns and thus independent of crop spatial arrangement and density. Increments in A. cristata seedbank can be reduced by planting soyabean at narrower row spacings and by bringing forward soyabean harvest. The first practice reduces A. cristata biomass and consequently seed production, and the second practice decreases the amount of seeds contributing to the soil seedbank.